Two new species of freshwater amphipods (Crustacea: Gammaridae) from Central Asia, with comments on the unusual upper lip morphology - Sidorov, Dmitry A. (Zootaxa, 2012)
This paper describes two new species of the genus Gammarus Fabricius from the freshwaters of Central Asia: G. montaniformissp. nov. (Kazakhstan, Dzungarian Alatau, Borohudzyr River) and G. alius sp. nov. (Kyrgyzstan, Chatyr-Kul Lake). The mor-phology of the mouth parts of the new species G. alius is characterised by a peculiar upper lip with “hooks” on its epistome thatis discussed. The affinity of the new species for their congeners is discussed, emphasizing morphological and biogeographical relationships.